PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK PERKIRAAN KEJADIAN LUAR BIASA PENYAKIT DEMAM BERDARAH DENGUE DI KOTA YOGYAKARTA - Dyah Respati Suryo Sumunar (Jurnal Penelitian Humaniora, 2009)
Intention of this research is: (1) Knowing factors what influencing incidence case of disease DBD at one particular area settlement, (2) Knowing how Geographical Information System benefit for the management of data spatial especially related to disease DBD of through estimation of data spatial, and (3) Knowing technological role of remote sensing and Geographical Information System can be exploited to conduct the estimation or estimate to the happening of extraordinary occurrence (KLB) DBD. Method used in this research represents the merger among interpretation aerial photograph and work the field. Interpretation aerial photograph conducted to recognize the habitat of propagation of mosquito through parameter of settlement pattern, settlement density, and vegetation. Work the field conducted for the acquirement of data irrigate, rainfall, and place of exile garbage, beside as correctness for interpretation aerial photograph. Other; Dissimilar data needed by place height, rainfall and density. Analyses the data conducted with the standing method (scoring) and join with others to compile the (overlay) use the geographical information system with the program of Arc View. Result of research indicate that there are five ( 5) class mount the regional crisis to occurrence of KLB DBD, namely class do not crisis, a few/little crisis, rather crisis, crisis, and very crisis. Area which is a few/little crisis represent the widest area, or for the width of 31,83% from all of research area, whereas area which do not crisis is 22,37%, rather area of crisis 24,46%, area crisis 19,84% and area of very crisis is 1,53%. Because area which crisis and rather crisis, crisis and very crisis also wide enough 1489,475 ha (45,63%) hence need there is care early society and Yogyakarta town to epidemic of disease DBD which possibility will be able to generate KLB.